Knowledge exchange partnership leads to digital transformation at Hydro‐X Water Treatment, Ltd. Issue 4 (10th April 2018) - Heinze, Aleksej; Griffiths, Marie; Fenton, Alex; Fletcher, Gordon
Abstract : To attract a generation of workers and consumers who have never known a world without Wi‐Fi, smartphones, or social media, organizations increasingly have no choice but to incorporate digital technology into every aspect of their operations and processes. The leaders of Hydro‐X, a privately owned British enterprise, met the challenge of digital transformation by forming a knowledge exchange partnership with a local university and applying two business models to assess the current state of digital maturity at the firm and map out a strategy to improve it. Their experiences reflect the HINGE project planning methodology: Horizon scanning to evaluate the competition, Internal auditing, New model creation, Gap analysis, and Evaluation of options to determine next steps. As a result of their efforts, Hydro‐X fostered an intrapreneurial spirit among its staff and refined its e‐commerce platform to digitally target key audiences in order to tap into a new source of revenue.